2019
DOI: 10.33830/jmst.v20i1.89.2019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Kesesuaian Lahan Untuk Rehabilitasi Hutan Mangrove Kota Langsa Aceh

Abstract: Mangrove ecosystem has  the role of interface ecosystem between land and sea. It has social, economic and ecological functions. The decreasing quality and quantity of mangrove mangrove forrest has resulted in environmental damage. Langsa City has mangrove forest in damaged condition because of conversion into fish ponds, illegal logging, pollution and settlements. The purpose of this research was to determine the level of land suitability of rehabilitated mangrove areas. The research was conducted in Langsa Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“…In this study, the type of sediment obtained is predominantly clay type. Clay substrate is very suitable for the growth of mangrove species Rhizophora spp., Brugueira spp., Avicennia spp, N. fruticans, and S. caseolaris [14]. Carbon and organic material of sediment samples were analyzed using the Walkley-Black method.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the type of sediment obtained is predominantly clay type. Clay substrate is very suitable for the growth of mangrove species Rhizophora spp., Brugueira spp., Avicennia spp, N. fruticans, and S. caseolaris [14]. Carbon and organic material of sediment samples were analyzed using the Walkley-Black method.…”
Section: Resultsmentioning
confidence: 99%
“…The area of mangrove forest on Manomadehe Island has been partially converted into sea transportation lanes, and the amount of residential waste around the mangrove area has resulted in reduced diversity of mangroves. Siringoringo et al (2017); Iswahyudi et al (2019) suggested that anthropogenic influences in the form of land clearing for aquaculture and settlements affect the number of mangrove species in an area. Giri et al (2015) found that anthropogenic activities greatly affected the extent and cover of mangroves in South Asia.…”
Section: Mangrove Distributionmentioning
confidence: 99%
“…Based on data from the Marine and Fisheries Office of West Lombok District (2016); Syarifuddin and Zulharman (2012); Imran and Ismail (2016) show that the dominant mangrove species in Lembar Village is Rhizophora sp with an important value index of 78.00%. Rhizophora mucronata is a species of mangrove whose growth is tolerant of environmental conditions, especially on sandy mud substrates, and it has widespread seeds with the seeds that can germinate while still in parent trees (Usman et al 2013;Iswahyudi et al 2019).…”
Section: Ecological Suitability For Mangrove Ecotourism Activitiesmentioning
confidence: 99%